(untitled) (World Conference on Engineering and Technological Sciences, 2026)
This scientific study analyzes the methods for calculating the technical and economic indicators of machine systems, their theoretical foundations, and practical application possibilities. The research examines deterministic and stochastic approaches, as well as life cycle cost (LCC)-based evaluation methods, highlighting their advantages and limitations. In addition, the study considers issues of technical justification of machine complexes used in construction processes, particularly in earthworks during the construction of residential buildings. Based on the analysis of scientific literature, the limitations of existing approaches are identified, and the necessity of an integrated assessment of machine systems is substantiated. The results of the study contribute to improving the efficiency of machine systems, reducing costs, and optimizing production processes.